Population modelling and genetics of a critically endangered Madagascan palm Tahina spectabilis. Issue 6 (2nd March 2020) - Shapcott, Alison; James, Heather; Simmons, Laura; Shimizu, Yoko; Gardiner, Lauren; Rabehevitra, David; Letsara, Rokiman; Cable, Stuart; Dransfield, John; Baker, William J.; Rakotoarinivo, Mijoro
Abstract: Madagascar is home to 208 indigenous palm species, almost all of them endemic and >80% of which are endangered. We undertook complete population census and sampling for genetic analysis of a relatively recently discovered giant fan palm, the Critically Endangered Tahina spectablis in 2008 and 2016. Our 2016 study included newly discovered populations and added to our genetic study. We incorporated these new populations into species distribution niche model (SDM) and projected these onto maps of the region. We developed population matrix models based on observed demographic data to model population change and predict the species vulnerability to extinction by undertaking population viability analysis (PVA). We investigated the potential conservation value of reintroduced planted populations within the species potential suitable habitat. We found that the population studied in 2008 had grown in size due to seedling regeneration but had declined in the number of reproductively mature plants, and we were able to estimate that the species reproduces and dies after approximately 70 years. Our models suggest that if the habitat where it resides continues to be protected the species is unlikely to go extinct due to inherent population decline and that it will likely experience significant population growth after approximately 80 years due to the reproductive and life cycle attributes of the species. The newly discovered populations contain more genetic diversity than the first discovered southern population which is genetically depauperate. The species appears to demonstrate a pattern of dispersal leading to isolated founder plants which may eventually lead to population development depending on local establishment opportunities. The conservation efforts currently put in place including the reintroduction of plants within the species potential suitable habitat if maintained are thought likely to enable the species to sustain itself but it remains vulnerable to anthropogenic impacts. Abstract : We studied the genetics, population ecology and suitable habitat for Tahina spectabilis a critically endangered palm from Madagascar to assess its long term viability. We found that current conservation measures may enable the species to persist. Its endangerment is not due to intrinsic population decline.